2021
DOI: 10.3389/fmolb.2021.775304
|View full text |Cite
|
Sign up to set email alerts
|

5-Methylcytosine RNA Methyltransferases-Related Long Non-coding RNA to Develop and Validate Biochemical Recurrence Signature in Prostate Cancer

Abstract: The effects of 5-methylcytosine in RNA (m5C) in various human cancers have been increasingly studied recently; however, the m5C regulator signature in prostate cancer (PCa) has not been well established yet. In this study, we identified and characterized a series of m5C-related long non-coding RNAs (lncRNAs) in PCa. Univariate Cox regression analysis and least absolute shrinkage and selector operation (LASSO) regression analysis were implemented to construct a m5C-related lncRNA prognostic signature. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…These TNF-related lncRNAs were involved in carcinogenesis, and inflammatory and immune responses (22)(23)(24)(25). A number of studies have also demonstrated that some of TNF-related lncRNAs are closely associated with cancer proliferation and survival (32)(33)(34)(35)(36)(37)(38). Thus, we analyzed the expression patterns and clinical significance of TNFrelated lncRNAs in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…These TNF-related lncRNAs were involved in carcinogenesis, and inflammatory and immune responses (22)(23)(24)(25). A number of studies have also demonstrated that some of TNF-related lncRNAs are closely associated with cancer proliferation and survival (32)(33)(34)(35)(36)(37)(38). Thus, we analyzed the expression patterns and clinical significance of TNFrelated lncRNAs in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidence over the two decades suggested that various types of RNA modifications, such as 5-methylcytosine (m 5 C), m 6 A, inosine (I), and 2′-O-methylation (2′-O-Me) are implicated in PCa (6,(36)(37)(38). Among them, 6 A has attracted the most attention due to the wide distribution of this modification across the human transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…The ceRNA regulatory role of long non-coding RNA (lncRNA) in T2D has been identified ( Lin et al, 2017 ). Recent studies revealed that m5C-related lncRNA signatures play important role in human cancers ( Wang et al, 2021 ; Zheng et al, 2022 ). In this study, we constructed a ceRNA interaction network.…”
Section: Discussionmentioning
confidence: 99%